Management of Inter-Religious Harmony through Multicultural Leadership Roles: A Case Study of Hindus’ Way of Celebrating Diversity in Takbiran Parade - Fitriani, Mohamad Iwan (JURNAL PENELITIAN KEISLAMAN, 2023)
This research was conducted in Narmada District, West Lombok in 2019. It’s based on fact relates to the participation of Hindus in the Muslim takbiran parade called as celebrating diversity. This study uses a qualitative-phenomenological approach with mono-multi-inter-religious, inter-religious dialogue, and intercultural competence theory as analytical theories. Furthermore, this study found that: (1) when Hindus understand, live, and practice their own religious teachings well while finding a meeting point between their religion and other religions and they’re willing to take part in certain rituals (not all rituals); and (2) leaders’ roles to manage interreligious harmony are spokesman role, disturbance handler and dissemination’s role. This study concludes that celebrating diversity is one of the ideal portraits of a multi-religious society that needs to be habituated based on certain agreements in certain agreed rituals among different religions. A multicultural insight and behavior of a leader in multi-religious society is needed.